PENGARUH TRIPLE BOTTOM LINE, ENVIRONMENTAL ACCOUNTING TERHADAP CORPORATE SOCIAL RESPONSIBILITY - Muhammad Ash Habul Kahfi; Sofyan Syamsuddin; Sahrir Sahrir; Indah Pratiwi (Media Bina Ilmiah, 2023)
Environmental Accounting or also known as Green Accounting is part of the company's accounting itself, namely by including costs related to the environment into the company's accounting. Corporate Social Responsibility from the perspective of the Triple Bottom Line and Environmental Accounting, in carrying out its operational activities, the company certainly does not only focus on Profit, but must pay attention to the State of the Environment (Planet) and Society (People) in the area where the company stands in specifically. Collecting data in this study used an online questionnaire through the Google form which was distributed to respondents. There are twenty-four indicators that are used to see how far the influence of the Triple Bottom Line, Environmental Accounting influences Corporate Social Responsibility activities at PT Pertamina Patra Niaga Fuel Terminal Palopo. Questionnaires were distributed using a Likert scale from 1 (very ignorant) to 5 (very knowledgeable). Based on the research results above, it can be concluded that the Triple Bottom Line variable has a significant influence on the implementation of the Corporate Social Responsibility program. The Environmental Accounting variable does not have a very significant influence on the implementation of the Corporate Social Responsibility program because in the implementation of CSR the community will pay more attention to what is given to them and the environment, but do not know about how the allocation is related to the costs incurred to implement this CSR program.